Controlling Immigrant Integration in the Euro-Mediterranean Region: A Compelling Turnaround in Times of Economic Crisis - Spina,Encarnación La (2017)
The Euro-Mediterranean region has become one of the most critical areas in the European Union on the issue of attracting migrants and experiencing the subsequent migratory pressures, but this has had very little impact on major comparative studies of European integration policies. Greece, Italy, Spain and Portugal are easily identifiable as exponents of a ‘non-model' system of integration. This trend changed on an academic and political level in the period from 2003 to 2009. Southern European countries have yet to establish nationwide integration policies for immigrants, and in times of economic crisis they have strongly restricted welfare protection, even though social rights are keystones for immigrant integration. Looking mainly at the Euro-Mediterranean region, this paper aims to analyse crossed interactions, to detect strengths, weaknesses, opportunities and threats in the emulation of nationalistic models in order to boost immigrant integration through equal access to social rights.